The effect of bioresorbable vascular scaffold implantation on distal coronary endothelial function in dyslipidemic swine with and without diabetes. (1st February 2018) - van den Heuvel, Mieke; Sorop, Oana; van Ditzhuijzen, Nienke S.; de Vries, René; van Duin, Richard W.B.; Peters, Ilona; van Loon, Janine E.; de Maat, Moniek P.; van Beusekom, Heleen M.; van der Giessen, Wim J.; Jan Danser, A.H.; Duncker, Dirk J.
Abstract: Background: We studied the effect of bioresorbable vascular scaffold (BVS) implantation on distal coronary endothelial function, in swine on a high fat diet without (HFD) or with diabetes (DM + HFD). Methods: Five DM + HFD and five HFD swine underwent BVS implantation on top of coronary plaques, and were studied six months later. Conduit artery segments > 5 mm proximal and distal to the scaffold and corresponding segments of non-scaffolded coronary arteries, and segments of small arteries within the flow-territory of scaffolded and non-scaffolded arteries were harvested for in vitro vasoreactivity studies. Results: Conduit segments proximal and distal of the BVS edges showed reduced endothelium-dependent vasodilation as compared to control vessels ( p  ≤ 0.01), with distal segments being most prominently affected ( p  ≤ 0.01). Endothelial dysfunction was only observed in DM ± HFD swine and was principally due to a loss of NO. Endothelium-independent vasodilation and vasoconstriction were unaffected. Surprisingly, segments from the microcirculation distal to the BVS showed enhanced endothelium-dependent vasodilation ( p  < 0.01), whereas endothelium-independent vasodilation and vasoconstriction were unaltered. This enhanced vasorelaxation was only observed in DM + HFD swine, and did not appear to be either NO- or EDHF-mediated. Conclusions: Six months of BVS implantation in DM + HFD swine causes NO-mediated endothelial dysfunction in nearby coronary segments, which is accompanied by a, possibly compensatory, increase in endothelial function of the distal microcirculation. Endothelial dysfunction extending into coronary conduit segments beyond the implantation-site, is in agreement with recent reports expressing concern for late scaffold thrombosis and of early BVS failure in diabetic patients.